Highly robust silicon bimorph plate anode and its mechanical analysis upon electrochemical lithiation - Kim, Yeongae (2020)
As the need for smaller, lighter, and longer lasting energy storage increases, silicon (Si) rises as a promising anode material of lithium (Li) ion batteries due to large specific capacity. However, the Si undergoes severe volume expansion causing mechanical fracture and electrochemical degradation. The use of nanostructured Si prevents mechanical fracture, but its large surface area enables irreversible side reaction. Therefore, understanding the mechanical behavior of lithiated Si (LixSi) is essential for designing robust Si structures with less surface area. Here, we estimate the stress in LixSi on crystalline-Si (c-Si) and copper bimorph plate and study its fracture resistance. When LixSi and c-Si coexisted, LixSi exhibits ~ 50 % of the full lithiation and compression of ~ 0.55 GPa, which is smaller than its yield strength. After c-Si is removed, it is predicted that plastic deformation of LixSi would occur on the open surface of the plate, but most of the structure would remain in the elastic behavior regime. The low stress in the LixSi plate allows it to bear fractures up to much larger size (~ 2 μm) than that of Si nanoparticles and nanopillars. It suggests using the robust micron-scale silicon structure for highly reversible and cost effective anode of Li-ion batteries.